2022
DOI: 10.1021/acsomega.1c04270
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Metallurgical Coke Reactivity Index (CRI) and Coke Strength after Reaction (CSR): An Experimental Study

Abstract: The coke reactivity index and coke strength after reaction are critical parameters for the efficient operation of a blast furnace. Therefore, maintaining desired qualities of the produced coke as per coal blend chemistry and coke oven battery parameters is essential. However, the coke reactivity index (CRI) and coke strength after reaction (CSR) vary from laboratory to laboratory even though they have the same determination methodology. In the present investigation, a unique laboratory sample holder for reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Resistivity and reactivity are different in nature. For example, the analyses of many studies [17][18][19] show that the properties of the coal used (ash content, sulfur content, mineral composition, volatile yield, and petrographic composition), the technology of the batch preparation, the thermal regime of its coking, and the coking period affect the CRI. At the same time, both of these indicators change synchronously because they are influenced by some common factors, such as the temperature level and coke readiness, which indicates the orderliness of its structure.…”
Section: Discussionmentioning
confidence: 99%
“…Resistivity and reactivity are different in nature. For example, the analyses of many studies [17][18][19] show that the properties of the coal used (ash content, sulfur content, mineral composition, volatile yield, and petrographic composition), the technology of the batch preparation, the thermal regime of its coking, and the coking period affect the CRI. At the same time, both of these indicators change synchronously because they are influenced by some common factors, such as the temperature level and coke readiness, which indicates the orderliness of its structure.…”
Section: Discussionmentioning
confidence: 99%
“…The critical factor determining the normal operation of BF is ∆P/H. In order to quantify the permeability of the furnace charge, the permeability of burden was calculated by the Ergun equation [25], which is shown by Equation (7), where d p , u, ε, ρ, µ, φ were defined as particle diameter, gas velocity, void fraction, density, viscosity, and the shape factor, respectively. Furthermore, the coke average diameter was 10 mm, the void fraction was 0.418, and the shape factor was 0.785, as is shown in the research of Yamada [26].…”
Section: Mathematical Model Of Permeabilitymentioning
confidence: 99%
“…The dissected blast furnace [ 5 ] showed that the coke solution loss reaction influenced the gas permeability of the upper part of BF [ 6 , 7 , 8 ], and there are many references available in this field [ 9 , 10 ]. In addition, the thickness of the coke layer is also an important factor affecting the distribution of gas flow.…”
Section: Introductionmentioning
confidence: 99%
“…The CSR and CRI of the coke also fall, although fluidity marginally improves as a result of lowering the particle size of the biochar. A range of 2-4 mm was determined to be the ideal particle size for biochar [135].…”
Section: The Challenges and Future Prospects In The Application Of Li...mentioning
confidence: 99%